CLINICAL PHARMACOLOGICAL APPROACH TO THE USE OF IMMUNOCORRECTORS IN IMMUNE INFLAMMATORY DISEASES (World Bulletin of Public Health, 2024)
The review presents the results of a comprehensive study of the main properties of the therapeutic molecule azoximer bromide (polyoxidonium). The experience of using the immunomodulator in acute respiratory infections is analyzed. Polyoxidonium has a pronounced immunomodulatory (including interferon-producing) activity, has a non-specific protective effect against a wide range of pathogens, based not on direct inhibition of microorganisms, but on the regulation of the immunity of the macroorganism. In addition, the drug has antitoxic and antioxidant properties. In the acute period of the disease, azoximer bromide is used in combination with etiotropic therapy, and during the rehabilitation period or for the purpose of immunoprophylaxis of respiratory infections - as monotherapy.
Keywords: respiratory infections; resistance; immunity; immunomodulators